2011
DOI: 10.1007/s10165-011-0502-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse alveolar damage in patients with dermatomyositis: a six-case series

Abstract: The clinical course of diffuse alveolar damage (DAD) was studied in six consecutive cases of dermatomyositis (DM) based on our hospital records over 8 years. Three patients had severe myopathy at presentation, and the other three patients showed clinically amyopathic DM (CADM). Interstitial pneumonia in all patients developed shortly after they manifested DM. DAD in five deceased patients, which was proven pathologically, did not respond to steroid therapy combined with cyclosporine or tacrolimus. Of these, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…Pathologically, DAD is also evident in rapidly progressive ILD associated with ADM (15,16). A novel autoantibody, anti-CADM-140, was identified and patients with the antibody frequently had ADM with rapidly progressive ILD (17).…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, DAD is also evident in rapidly progressive ILD associated with ADM (15,16). A novel autoantibody, anti-CADM-140, was identified and patients with the antibody frequently had ADM with rapidly progressive ILD (17).…”
Section: Discussionmentioning
confidence: 99%
“…administration of prednisolone 1 mg/kg bodyweight per day with or without methylprednisolone pulse therapy) together with a calcineurin inhibitor should be started (evidence level III-V). 28,79,81,[161][162][163][164][165] A blood trough level of 100-150 ng/mL for CsA 81,162 and 5-10 ng/mL for Tac 164 should be maintained unless renal damage is noted (evidence level III-V). Addition of intermittent i.v.…”
Section: Cq19 How Should Myositis Patients With Ild Be Treated?mentioning
confidence: 99%
“…Addition of intermittent i.v. CPA therapy (evidence level III-V) 81,[164][165][166] and/or IVIg (evidence level V) 28,167 should be attempted for serious or intractable cases. There are reports that high-dose GC therapy in combination with intermittent CPA therapy and cyclosporin was effective in treating rapidly progressive ILD with CADM (evidence level IV).…”
Section: Cq19 How Should Myositis Patients With Ild Be Treated?mentioning
confidence: 99%
“…Both drugs have been reported in case studies and small case series to be effective in the treatment of ILD associated with either polymyositis or dermatomyosistis. [62][63][64][65][66][67][68][69] The largest of these studies reports 15 cases (identified from a registry of 179 patients with myositis) of IIM-associated ILD treated with calcineurin inhibitors for a median of 24 months. The majority (11 cases) were being treated for refractory disease.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%